[Afisz. Incipit] Nie czcza gadanina, lecz nabywanie Premiowej Pożyczki ... (Gdańsk : [wydawca nieznany], 1946)
Sztrajfa propagandowa.
Keywords: Propaganda -- Polska -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1990.